Sub-chronic exposure to crude acetylene results in the development of deleterious cardio metabolic changes in Sprague Dawley rats - Gitonga, Caroline Gatwiri; Githinji, Charles; Chege, Boniface; Bukachi, Frederick; Waweru, Peter (PLOS ONE, 2025)
Objective Calcium carbide-derived acetylene is widely used as an artificial fruit ripening agent despite its potential health risks. This study aimed to investigate the effects of sub-chronic exposure to crude acetylene on cardiometabolic parameters using a rodent model. Methods Twenty-four male Sprague Dawley rats were randomized into four groups: control (no exposure) and three test groups exposed to 58,000 ppm crude acetylene for 10, 30, or 60 minutes daily over 42 days. Body weight, fasting blood glucose, oral glucose tolerance, hepatic triglyceride levels, adipose tissue mass, liver enzyme activity, and oxidative stress markers were assessed. Histopathological analysis of liver tissue was also conducted. Results Acetylene exposure did not significantly alter body weight but led to dose-dependent increases in central adiposity, hepatic triglycerides, and markers of oxidative stress. Higher doses were also associated with impaired glycemic control, elevated liver enzyme levels, and increased free heme concentration in plasma, suggesting oxidative damage and hemolysis. Histological analysis revealed central vein congestion and hepatic structural alterations in exposed groups. Conclusion Sub-chronic inhalation of crude acetylene induced metabolic dysfunction characterized by impaired glucose regulation, hepatic steatosis, and oxidative stress, despite no changes in overall body weight. These findings highlight the potential health risks associated with acetylene exposure and underscore the need for regulatory measures to limit its use in fruit ripening.